Specialized lambda transducing bacteriophage which carries hisS, the structural gene for histidyl-transfer ribonucleic acid synthetase. - Fishman, S E (1979)
A number of specialized lambda transducing bacteriophages which carry the Escherichia coli gene guaB were isolated from E. coli. One of these bacteriophages, lambda cI857 Sam7 d guaB-2, also carries hisS, the structural gene for histidyl-transfer ribonucleic acid synthetase (EC 6.1.1.21). Histidyl-transfer ribonucleic acid synthetase activities in induced and uninduced lysogens carrying lambda d guaB-2 indicate that the phage carries the entire structural gene and that the gene is under the control of an E. coli promoter. These conclusions were confirmed by the in vivo production of a protein encoded by the phage which comigrates with authentic histidyl-transfer ribonucleic acid synthetase on two-dimensional polyacrylamide gels.